MANAGEMENT OF POSTNATAL DEPRESSION WITH SADABUSAGA APPROACH - Riska Dwi Candrawati (Journal of Vocational Nursing, 2026)
Introduction: Postnatal depression (PND) is a psychological disorder commonly experienced by mothers during the first year after giving birth. This condition is associated with an increased risk of suicide, which is one of the leading causes of postnatal death. It requires psychotherapy as well as group and family support. Therefore, this study aims to determine the effect of the SADABUSAGA (Love and Support Mothers Together with Family) family intervention approach on PND in Indragiri Hulu District. Methods: This study used a pretest–posttest control group design. It was conducted from February to May 2025 on 30 postpartum mothers within one year after childbirth in Indragiri Hulu District, divided into 15 participants in the experimental group and 15 in the control group. Results: The average depression score in the experimental group before the intervention was 15.8 and decreased to 7.2 after the intervention. In the control group, the average score decreased from 10.6 to 9.7. The p-value from the independent t-test was 0.00 (<0.05), confirming that the SADABUSAGA family intervention significantly reduced depression in postpartum mothers. Conclusions: Family support, especially from husbands, parents, and in-laws through the SADABUSAGA approach, can help prevent and manage PND in postpartum mothers.